Livestock Exchange hard seat 2011: Carlos Sere on his time at ILRI - Seré Rabé, Carlos (International Livestock Research Institute, 2011)
On 9 and 10 November 2011, the ILRI Board of Trustees held a 2-day 'liveSTOCK Exchange' to discuss and reflect on livestock research for development. During the event, Brian Perry interviewed former ILRI Director General Carlos Seré on his previous leadership at ILRI.